Small mammals feeding on hypogeous fungi - Połatyńska, Małgorzata (Acta Universitatis Lodziensis. Folia Biologica et Oecologica, 2014)
Fungi serve as a food source for a wide variety of animals. Among mammals, most species feed on fungi occasionally or accidentally while foraging for other type of food, but some species are frequent mycophags and fungi can be a dominant component of their diet. Examples of mycophags can be found among marsupials: wallabies and bettongs; and rodents: squirrels, chipmunks, voles and mice. Hypogeous fungi produce closed, underground sporocarps without opening mechanisms, and thus are unable to release their spores into the air. In case of those fungi, animals feeding on sporocarps and spreading spores in their faeces are considered to be the main vector of spore dispersal. Animals that frequently feed on fungi and other heavy digestible food have developed morphological adaptations such as longer gut retention and a spiral construction of the proximal colon, to digest more fungal material which is rich in nitrogen. The spores stay viable after passing through the animal gut, and in some cases their ability to germinate and form mycorrhiza is enhanced after leaving the intestine. Hypogeous fungi are mycorrhizal partners for plants and it is therefore possible that the interactions between mycorrhizal fungi and animals spreading their spores also play an important role in ecosystem functioning.